How does technological parameters impact the static current gain of InP-based Single Heterojunction Bipolar Transistor? - Jihane Ouchrif; Abdennaceur Baghdad; Aicha Sahel; Abdelmajid Badri; Abdelhakim Ballouk (International Journal of Electrical and Computer Engineering (IJECE), 2019)
In telecommunication systems, Heterojunction Bipolar Transistors (HBTs) are used extensively due to their good electrical characteristics. The work presented in this paper aims to enhance the electrical performance of the InP / InGaAs Single Heterojunction Bipolar Transistor (SHBT) in terms of the static current gain β. Silvaco’s TCAD tools were used for the simulation of the output characteristics of the studied electronic device. Initially, we used the interactive tool Deckbuild to define the simulation program and the device editor DevEdit to design the device structure, and we also used the simulator Atlas which allows the prediction of the electrical characteristics of most semiconductor devices. Because of several phenomena occuring within the electronic device SHBT, we added some physical models included in the simulator such as SRH, BBT.STD. Afterwards, we investigated the influence of doping concentrations of the base and the collector Nb and Nc on the electrical performance of the InP/InGaAs SHBT, and particularly in terms of the static current gain β. Finally, based on optimal values of the selected parameters, we have defined an optimized device that has a highest current gain β.